COULOMB INTERACTIONS AT THE SILICON WIRE-NERVOUS TISSUE INTERFACE - Klimovskaya, A.I.; Chaikovsky, Yu.B.; Naumova, O.V.; Vysotskaya, N.A.; Korsak, A.V.; Likhodiievskyi, V.V.; Fomin, B.I. (World of Medicine and Biology, 2015)
In the past decade the “silicon crystal-nervous tissue” interface has been attracting huge interest due to the possibility of its application for neuro-computing and regenerative medicine. The key challenge of this research is to understand the mechanisms of the interface formation, and thus to prespecify properties of the interface and its operation. Despite numerous researches there is no clear definition of these mechanisms up to date. Here we present the study of the “silicon wire-nerve tissue” interface formed both in vivo and in vitro experiments. We have shown experimentally that there is a very good electrostatic adhesion of a nerve tissue to silicon wire in the living organism and in a medium, close to the physiological environment, as well.